2012
DOI: 10.1029/2012ms000154
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the climate of a global model

Abstract: [1] During a development stage global climate models have their properties adjusted or tuned in various ways to best match the known state of the Earth's climate system. These desired properties are observables, such as the radiation balance at the top of the atmosphere, the global mean temperature, sea ice, clouds and wind fields. The tuning is typically performed by adjusting uncertain, or even non-observable, parameters related to processes not explicitly represented at the model grid resolution. The practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
426
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(457 citation statements)
references
References 82 publications
9
426
1
Order By: Relevance
“…The values for individual models from CMIP5 are also displayed with the black markers. These results highlight the ability of different simulations to have similar climates but differing climate sensitivities [Mauritsen et al, 2012;Zhao et al, 2016].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 74%
“…The values for individual models from CMIP5 are also displayed with the black markers. These results highlight the ability of different simulations to have similar climates but differing climate sensitivities [Mauritsen et al, 2012;Zhao et al, 2016].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 74%
“…In a series of test simulations optimized values of the following parameters have been identified that lead to an almost balanced radiation budget at the TOA: the relative convective cloud mass flux above level of non-buoyancy (cmfctop = 0.35, default: 0.30, possi- ble range: 0.10-0.38) and the entrainment rate for deep convection (entrpen = 0.5 × 10 −4 m −1 , default: 1.0 × 10 −4 m −1 , possible range: 0.3-3.0 × 10 −4 m −1 ). The values for the possible ranges of these two parameters have been tested by Mauritsen et al (2012). Both changes, increasing the parameter cmfctop and decreasing the parameter entrpen, increase the net SW radiation at TOA, as the low-level clouds tend to be less and thinner.…”
Section: Balancing the Radiation Budgetmentioning
confidence: 99%
“…With this kind of model set-up the negative imbalance can be reduced by increasing the net SW radiation through changes of the parameters that affect cloud properties, thus reducing the planetary albedo. There are a number of parameters in the Tiedtke convection parameterization, which have an influence on the net SW radiation, as summarised by Mauritsen et al (2012). In a series of test simulations optimized values of the following parameters have been identified that lead to an almost balanced radiation budget at the TOA: the relative convective cloud mass flux above level of non-buoyancy (cmfctop = 0.35, default: 0.30, possi- ble range: 0.10-0.38) and the entrainment rate for deep convection (entrpen = 0.5 × 10 −4 m −1 , default: 1.0 × 10 −4 m −1 , possible range: 0.3-3.0 × 10 −4 m −1 ).…”
Section: Balancing the Radiation Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…For decadal forecasting, a stand-by model system for rapid model-based assessment of the decadal scale climate impact is needed, in case of any major volcanic eruption. However any modification to the climate model itself requires a retuning (Mauritsen et al, 2012), a new control run with constant forcing to make sure the model simulates a stable climate, and a new ensemble of historical runs as a reference for assessing skill enhancement through initialization (Goddard et al, 2013;Illing et al 2014). 15…”
Section: Introductionmentioning
confidence: 99%